Circular RNA expression alterations and function prediction in OSA-induced pancreatic injury in mice: New insights into pathogenesis. - Qingshi Chen; Jiayu Lin; Zhiyu Chen; Lishuang Che; Dexin Liu (PLoS ONE, 2023)
Objectives Increasing studies have shown that circular RNAs (circRNAs) participate in the pathogenesis and progression of many diseases. However, the function of circRNAs in obstructive sleep apnea (OSA)-induced pancreatic damage has not been fully elucidated. In this study, the altered circRNA profiles in a chronic intermittent hypoxia (CIH) mouse model were investigated, aiming to provide novel clues for delineating the underlying mechanisms of OSA-induced pancreatic injury. Methods A CIH mouse model was established. circRNA microarray was then applied to profile circRNA expression in pancreatic samples from CIH groups and controls. Our preliminary findings were validated by qRT-PCR. Subsequently, GO and KEGG pathway analyses were carried out to annotate the biological functions of target genes of circRNAs. Lastly, we constructed a circRNA-miRNA-mRNA (ceRNA) network according to the predicted circRNA-miRNA and miRNA-mRNA pairs. Results A total of 26 circRNAs were identified to be differentially expressed, with 5 downregulated and 21 upregulated in the CIH model mice. Six selected circRNAs were preliminarily used to confirm the results by qRT-PCR, which were consistent with microarray. GO and pathway analysis indicated that numerous mRNAs were involved in the MAPK signaling pathway. The ceRNA analysis displayed the broad potentials of the dysregulated circRNAs to modulate their target genes by acting as miRNAs sponges. Conclusions Taken together, our study first revealed the specific expression profile of circRNAs in CIH-induced pancreatic injury, which suggested a novel focus for investigating the molecular mechanism of OSA-induced pancreatic damage through modulating circRNAs.